1982
DOI: 10.1021/bi00540a013
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome c oxidase binding of hydrogen peroxide

Abstract: Oxidized cytochrome c oxidase can bind hydrogen peroxide, as evidenced by changes in its spectrum and its ability to use hydrogen peroxide as an electron acceptor in cytochrome c oxidation. The affinity of the oxidized enzyme for hydrogen peroxide is high, with a Kd of less than 10 microM, and the binding is inhibited by ligands of cytochrome a3. Oxidized cytochrome c oxidase, in submitochondrial particles or solubilized in several ionic and nonionic detergents, binds peroxide with comparable affinities. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(57 citation statements)
references
References 35 publications
7
50
0
Order By: Relevance
“…The peak-to-trough magnitude of the H 2 O 2 -induced difference spectra in the Soret band was typically 30-45 mM Ϫ1 cm Ϫ1 in the WT and in the K channel mutants as compared with ca. 50 mM Ϫ1 cm Ϫ1 observed for beef heart enzyme (29,(42)(43)(44) Before the flash, the sample was incubated for several minutes with 1 mM H2O2 to convert heme a3 to the ferryl-oxo state. After recording a trace (Wildtype), 1 mM potassium cyanide was added and the second trace (ϩKCN) was recorded.…”
Section: Resultsmentioning
confidence: 99%
“…The peak-to-trough magnitude of the H 2 O 2 -induced difference spectra in the Soret band was typically 30-45 mM Ϫ1 cm Ϫ1 in the WT and in the K channel mutants as compared with ca. 50 mM Ϫ1 cm Ϫ1 observed for beef heart enzyme (29,(42)(43)(44) Before the flash, the sample was incubated for several minutes with 1 mM H2O2 to convert heme a3 to the ferryl-oxo state. After recording a trace (Wildtype), 1 mM potassium cyanide was added and the second trace (ϩKCN) was recorded.…”
Section: Resultsmentioning
confidence: 99%
“…Species A then reacts further to yield intermediate P (Compound C, peroxo form), originally assumed to be a peroxo species. This form has also been generated independently from the addition of hydrogen peroxide to oxidized or reduced enzyme (12,140,141), or by the partial reversal of dioxygen chemistry under conditions of high thermodynamic driving force in the reverse direction SCHULTZ CHAN (134,136). It is characterized by an absorption maximum at 607 nm in the optical difference spectrum of the enzyme.…”
Section: Reaction Of the Enzyme With Dioxygenmentioning
confidence: 99%
“…Orii & King studied the decay process of the "oxygenated oxidase" and found that it decays in two distinct steps (114,115). More recently, Bickar et al, unaware of the earlier work of Okunuki & Orii, reinvestigated the reaction of cytochrome oxidase with H202 (116). They found that resting oxidase binds some H202> whereas the pulsed state (reduced and reoxidized) binds H202 more efficiently and more quickly.…”
Section: The "Peroxy" Intermediatementioning
confidence: 99%